ECG signal base line filtering and power interference suppression method - Min Li; Jiyin Zhao; Weiwei Zhang; Ruirui Zheng (The 2nd International Conference on Information Science and Engineering, 2010)
ECG signal is non-stationary, base line drift and power interference are the important factors influencing ECG signal extraction in high accuracy and directly determine the accuracy of ECG signal extraction and performance of analyzing and processing ECG signal. Adaptive filtering method can realize effective extraction of non-stationary signals without knowing a priori knowledge about signal and noise, this paper presents an adaptive noise cancellation system for ECG signal base line filtering and power interference suppression, constructs an iterative time LMS algorithm combining variable and fixed step size, which effectively solves the problems of filtering SNR and convergence rate. The experiment results show that this method improves 26.36dB in SNR, eliminates base line drift and power interference effectively, extracts ECG signal accurately and converges quickly, has important practical value in medical clinical diagnosis.